2016
DOI: 10.1111/jvim.13965
|View full text |Cite
|
Sign up to set email alerts
|

Association between Body Condition Score and Cancer Prognosis in Dogs with Lymphoma and Osteosarcoma

Abstract: BackgroundIn humans and rodents obesity appears to promote some cancers by increasing incidence, tumor aggressiveness, recurrence, and fatality. However, the relationship between obesity and cancer in dogs has not been thoroughly evaluated.Hypothesis/ObjectivesWhether body condition score (BCS) at the time of lymphoma (LSA) or osteosarcoma (OSA) diagnosis in dogs is predictive of survival time (ST) or progression‐free interval (PFI). We hypothesized that an overweight body state at the time of cancer diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 42 publications
1
36
0
Order By: Relevance
“…However, it has also been postulated that large size of adult animals and tall shoulder height is a more reliable predictive factor for the development of OSA than dog's breed (Rosenberg et al 2007, Eberle et al 2010, Kruse et al 2012, Rehbun et al 2016. In most studies male dogs are slightly more often affected with OSA than females (Spodnick et al 1992, Romano et al 2016, although there are publications which contradict this statement (Eberle et al 2010, Anfinsen et al 2011, Coyle et al 2013, Fenger et al 2014, Nagamine et al 2015. It was also suggested that in Rottweilers, Saint Bernards and Great Danes females suffer more commonly than males (Morello et al 2011).…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…However, it has also been postulated that large size of adult animals and tall shoulder height is a more reliable predictive factor for the development of OSA than dog's breed (Rosenberg et al 2007, Eberle et al 2010, Kruse et al 2012, Rehbun et al 2016. In most studies male dogs are slightly more often affected with OSA than females (Spodnick et al 1992, Romano et al 2016, although there are publications which contradict this statement (Eberle et al 2010, Anfinsen et al 2011, Coyle et al 2013, Fenger et al 2014, Nagamine et al 2015. It was also suggested that in Rottweilers, Saint Bernards and Great Danes females suffer more commonly than males (Morello et al 2011).…”
Section: Discussionmentioning
confidence: 93%
“…The mean age of dogs with OSA has been shown to range from 6 to 9 years (Anfinsen et al 2011, Romano et al 2016. Some studies have also implied that the age distribution of dogs with OSA has two peaks: the first between 18-24 months, and the second between 7-10 years, however, the majority of skeletal OSAs in dogs occur in the latter period (Dernall et al 2007, Culp et al 2014, Fanger et al 2014, Nagamine et al 2015.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations